Using metamorphic modelling techniques to investigate the thermal and structural evolution of the Himalayan-Karakoram-Tibetan orogen - Palin, RM (2013)
Metamorphic rocks constitute a vast volumetric proportion of the Earth’s continental lithosphere and are invaluable recorders of the mechanisms and rates of deformation and metamorphism that occur at the micro-, meso- and macro-scale. As such, they have the potential to provide detailed insight into important tectonic processes such as the subductive transport of material into, and back from, mantle depths and also folding, faulting and thickening of crust that occurs during collisional orogeny. The Himalayan-Karakoram-Tibetan orogen is the youngest and most prominent example of a continent-continent collisional mountain belt on Earth today and is a product of the on-going convergence of the Indian and Asian plates that initiated in the Early Eocene. Thus, it provides an exceptional natural laboratory for the investigation of such processes. Recent advances in the computational ability to replicate natural mineral assemblages through a variety of metamorphic modelling techniques have led to improvements in the amount (and quality) of petrographic data that may be obtained from a typical metamorphic rock. In this study, phase equilibria modelling (pseudosection construction) using THERMOCALC, amongst other techniques, has been integrated with in-situ U–Pb and Th–Pb geochronology of accessory monazite in order to constrain the tectonothermal evolution of four regions intimately associated with the Himalayan-Karakoram-Tibetan orogen. These regions comprise the Karakoram metamorphic complex (north Pakistan), the Tso Morari massif (north-west India), the eastern Himalayan syntaxis (south-east Tibet) and the Day Nui Con Voi metamorphic core complex of the Red River shear zone (North Vietnam). Each case study documents previously unreported metamorphic, magmatic or deformational events that are associated with the India-Asia collision. These data have allowed original interpretations to be made regarding the tectonic evolution of each individual region as well as the large-scale evolution of the Himalayan-Karakoram-Tibetan orogenic system as a whole.